Strategi Marketing dalam Usaha Meningkatkan Volume Transaksi Pelanggan dengan Menggunakan Mobile Fintech Application OVO - Lusiana Dianingsih (Universitas Tarumanagara, 2020)
This research aims to analyze the impact of product, price/cashback, promotion, and place to increase transaction volume. This research is quantitative by distributing questioner to 100 respondents who are using OVO application. Multiple linier regression is using by using t-test and f-test. The result of this research show that product, price/cashback, promotion, and place have a significant effect to purchase decision, with probability <0,05. Variable that have the greatest influence (dominant) of purchase intention is product.